2020
DOI: 10.1007/s00401-020-02126-w
|View full text |Cite
|
Sign up to set email alerts
|

T cell infiltration in both human multiple system atrophy and a novel mouse model of the disease

Abstract: Multiple system atrophy (MSA) is a progressive neurodegenerative disorder characterized by abnormal accumulation of alpha-synuclein (α-syn) in oligodendrocytes accompanied by inflammation, demyelination, and subsequent synapse and neuronal loss. Little is known about the mechanisms of neurodegeneration in MSA. However, recent work has highlighted the important role of the immune system to the pathophysiology of other synuclein-related diseases such as Parkinson's disease. In this study, we investigated postmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 64 publications
7
85
0
Order By: Relevance
“…Such an increase in the number of infiltrating T cells could mediate the decrease in phosphorylated α-syn pathology in the substantia nigra. This complements several reports associating altered T cell function with PD and MSA [21][22][23][24][25][26]57] and studies demonstrating activation of immune cells by pathogenic αsyn [27,31,58]. One such study measuring nigral neurodegeneration as the readout supports the hypothesis that immune cells can modulate neuroinflammation and neurodegeneration in PD mouse models [59].…”
Section: Discussionsupporting
confidence: 86%
“…Such an increase in the number of infiltrating T cells could mediate the decrease in phosphorylated α-syn pathology in the substantia nigra. This complements several reports associating altered T cell function with PD and MSA [21][22][23][24][25][26]57] and studies demonstrating activation of immune cells by pathogenic αsyn [27,31,58]. One such study measuring nigral neurodegeneration as the readout supports the hypothesis that immune cells can modulate neuroinflammation and neurodegeneration in PD mouse models [59].…”
Section: Discussionsupporting
confidence: 86%
“…A recent study in MSA patients also showed increased infiltration in the brain by CD4+ and CD8+ T cells. Similar results were observed in a viral vectormediated oligodendroglial α-syn expression mouse model, where genetic depletion of TCR-β+ or CD4+ T cells attenuated α-syn-induced inflammation and demyelination in vivo [73]. Taken together, these studies suggest that T cells play a key role in the neuroinflammatory process in synucleinopathies such as DLB, PD, and MSA.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study in MSA patients showed increased infiltration in the brain by CD4 + and CD8 + T cells. Similar results were observed in a viral vectormediated oligodendroglial α-syn expression mouse model, where genetic depletion of TCR-β + or CD4 + T cells attenuated α-syn-induced inflammation and demyelination in vivo [72]. Taken together, these studies suggest that T cells play a key role in the neuroinflammatory process in synucleinopathies such as DLB, PD, and MSA.…”
Section: Discussionsupporting
confidence: 79%
“…To better understand the role of NKT cells in synucleinopathies, follow up studies should be conducted where selected subtypes of T cells, such as NKT cells, are inactivated or deleted in animal models exhibiting α-syn accumulation, including transgenic, viral vector, and α-syn pff injection models. One such study was recently published in a model of MSA [72]. We have also previously shown that on the Rag2 −/− background, where the mice are unable to produce mature lymphocytes, our α-syn tg mice displayed considerably decreased α-syn pathology.…”
Section: Discussionmentioning
confidence: 52%